2022
DOI: 10.1021/acsanm.2c02137
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Nonclassical Ripples in Draped Graphene Nanosheets: Implications for Straintronics

Abstract: Ever since the discovery of graphene and subsequent explosion of interest in single-atom-thick materials, studying their mechanical properties has been an active area of research. Atomistic length scales often necessitate a rethinking of physical laws, making such studies crucial for understanding and ultimately utilizing material properties. Here, we report on the investigation of nanoscale periodic ripples in suspended, single-layer graphene sheets by scanning tunneling microscopy and atomistic scale simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Comparisons between flat and rippled graphene on copper surface showed that the binding of copper atoms is more favored by rippled graphene. The examples showing the good agreement in describing graphene bending, ripple formation as well as binding characteristic for copper surface were recently reported [29,317]. With the use of previously published parameter set where C-Cu interactions were optimized for Cu-metal surface catalysis [318], the authors were able to reproduce experimentally measured graphene draping and rippling angle at the copper step edges and also show better binding properties of the rippled graphene.…”
Section: D/3d and 3d/2d Heterostructuresmentioning
confidence: 62%
See 1 more Smart Citation
“…Comparisons between flat and rippled graphene on copper surface showed that the binding of copper atoms is more favored by rippled graphene. The examples showing the good agreement in describing graphene bending, ripple formation as well as binding characteristic for copper surface were recently reported [29,317]. With the use of previously published parameter set where C-Cu interactions were optimized for Cu-metal surface catalysis [318], the authors were able to reproduce experimentally measured graphene draping and rippling angle at the copper step edges and also show better binding properties of the rippled graphene.…”
Section: D/3d and 3d/2d Heterostructuresmentioning
confidence: 62%
“…2D materials exhibit many unique properties and play a pivotal role in a wide range of research areas such as sensors [319,320], desalination membranes [34,317,321,322], energy storage [323,324] and biomedical applications [325][326][327]. However, the mechanical properties of 2D materials cannot be accurately inferred from the chemical composition.…”
Section: Hybrid Ml/reaxff Applicationsmentioning
confidence: 99%
“…Triangular periodic ripples in suspended graphene were found in another work. There, bending was limited to a region few unit cells wide [94]. Triangular ripples are unlike the sinusoidal ripples found in fabrics.…”
Section: Cut and Folded Graphene: Sublattice And Valley Polarisationmentioning
confidence: 97%
“…Governed by the supernal flexibility of graphene, using the surface topographical corrugations like wrinkles [24,25], ripples [26][27][28][29][30][31][32][33], folds [34], or crumples [35][36][37][38] to exploit exceptional properties is an amazing technique in experiments. In particular, high-quality conformal wrinkles in graphene can be controllably fabricated with expected orientations, wavelengths, and amplitudes by using various simple methods, which is of paramount importance for potential applications in flexible electrodes, sensors, and actuators [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%